Economic impact of Chinese tourism on Australia: A new approach. Issue 6 (September 2018) - Van Hoa, Tran; Turner, Lindsay; Vu, Jo
China's trade, tourism and limited foreign direct investment (FDI) to Australia have been regarded as playing an important part in Australia's growth and prosperity in recent years. In spite of the fact that these activities are the three principal growth determinants in modern economic integration theory, growth studies based on this theory's structural framework, while highly appropriate, have hardly been undertaken. This article proposes to fill the gap by formally developing an endogenous causal model of simultaneous growth and tourism for policy analysis. In this model, trade, FDI and tourism are specified as the main contributing factors to growth. Simultaneously, gravity theory (including growth) and the Ironmonger–Lancaster new consumer demand theory determine tourism, while 'economic conditionality' potentially affecting both growth and tourism in the sense of Johansen is recognized and incorporated. The model is then applied to Australian and Chinese data for the important post-Japanese tourist boom period 1992–2015, to provide substantive findings on three questions: the impact of Chinese tourism to Australia, Chinese tourism determination and the effects of Chinese trade and key macroeconomic indicators on Australian economic growth. Significant policy implications are then developed for use by government tourism planners and policymakers.